2020
DOI: 10.3390/agronomy10050715
|View full text |Cite
|
Sign up to set email alerts
|

The Optimization of Nitrogen Fertilization Regulates Crop Performance and Quality of Processing Tomato (Solanum lycopersicum L. cv. Heinz 3402)

Abstract: In this study, we evaluated the effect of various fertilization regimes on processing tomato (Solanum lycopersicum L. cv. Heinz 3402) yield and quality by applying the following treatments: (i) control (C), (ii) conventional fertilizer (21-0-0, N-P-K) (CF), (iii) slow release nitrogen fertilizer 46-0-0 (SR), (iv) conventional fertilizer (21-0-0, N-P-K) + Zeolite (CFZ), and v) composted sheep manure (M). The results of the study showed that the SR and CFZ treatments resulted in the highest fruit yield per hecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 104 publications
4
17
0
Order By: Relevance
“…Our results are fully in agreement with those of Bililas et al [39], because we did not observe differences of this qualitative attribute of the color among different fertilization treatments (Table 2). In a study aimed at evaluating the optimization of nitrogen fertilization on crop performance and quality of processing tomato cv Heinz 3402, Petropoulos et al found an h • value ranging from 45.6 to 50.4 [40]. Moreover, Renna et al [41] reported an h • value of 48.2 for Manduria, an Italian local variety of processing tomato.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are fully in agreement with those of Bililas et al [39], because we did not observe differences of this qualitative attribute of the color among different fertilization treatments (Table 2). In a study aimed at evaluating the optimization of nitrogen fertilization on crop performance and quality of processing tomato cv Heinz 3402, Petropoulos et al found an h • value ranging from 45.6 to 50.4 [40]. Moreover, Renna et al [41] reported an h • value of 48.2 for Manduria, an Italian local variety of processing tomato.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen is an essential macronutrient that has to be replenished with fertilizer application before and during the growing period based on the cropping schedule of farmers [27,28]. In contrast to conventional crops, several studies have indicated the low requirements of wild or semi-domesticated species in nitrogen and agrochemical inputs, which further emphasize the importance of integrating such novel/alternative species in modern farming systems aiming at sustainable production of horticultural products [9,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the common application of N for enhanced crop yields has multiple implications on aspects such as the economy, the quality and the environment, therefore modern agriculture requires rational N management [ 3 , 4 ]. N has some negative consequences on the environment when misused, at the same time there are also economic implications that may affect crop productivity and the quality of the final product [ 16 , 17 ]. The application of fertilizer doses exceeding the crop needs may generate a situation where nitrates accumulate in the soil causing plant luxury consumption and low N use efficiency [ 11 , 18 , 19 ], while the excess of nitrates may be leached out of the root zone and contaminate the aquifer [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…N has some negative consequences on the environment when misused, at the same time there are also economic implications that may affect crop productivity and the quality of the final product [ 16 , 17 ]. The application of fertilizer doses exceeding the crop needs may generate a situation where nitrates accumulate in the soil causing plant luxury consumption and low N use efficiency [ 11 , 18 , 19 ], while the excess of nitrates may be leached out of the root zone and contaminate the aquifer [ 16 , 17 ]. The common application worldwide of soluble N fertilizer via the irrigation water (fertigation) with frequent delivery of small N doses directly in the root zone has the potential to improve the matching between fertilizer application and crop N demand, thereby minimizing both risks of economic loss and environmental pollution [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation